Adenosine deaminase. A pluridisciplinary enzyme. - da Cunha, J G (1991)
Adenosine deaminase is an enzyme that actively participates in the metabolism of the adenine nucleotides. It catalyzes the irreversible hydrolytic deamination of deoxyadenosine and adenosine with the production of deoxyinosine and inosine respectively and of ammonia. This enzyme thus plays an important role in lympho-monocyte maturation and activation. The increase in its activity in different biological fluids (pleural, pericardial, peritoneal, intra-articular and cerebrospinal fluids) has been used as a rapid diagnostic test in tuberculosis infection. In human immunodeficiency virus infection, it was verified that enzymatic activity progressively increases in serum and blood cells, accompanying the natural evolution of the disease. The physiopathological mechanism has not been definitely established but the CD4+ lymphocytes and macrophages are pointed to as being accountable for the enzyme's increase in activity. For this reason, adenosine deaminase could be a marker of the cellular immune response. The study of adenosine deaminase activity in blood cells elucidated the diagnosis of severe combined immunodeficiency (due to a congenital lack of the enzyme) in 30 to 50% of the cases. One type of congenital hemolytic anemia is due to an exaggerated enzymatic activity in red blood cells.